If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + x + -6 = -21 Reorder the terms: -6 + 2x + x = -21 Combine like terms: 2x + x = 3x -6 + 3x = -21 Solving -6 + 3x = -21 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3x = -21 + 6 Combine like terms: -6 + 6 = 0 0 + 3x = -21 + 6 3x = -21 + 6 Combine like terms: -21 + 6 = -15 3x = -15 Divide each side by '3'. x = -5 Simplifying x = -5
| -5m-11=1-3m | | 56+11m=80+8m | | (5x^2-6x+3)-(9x^2-6x+9)= | | 3x=833 | | -7(3)/-3 | | F+9.3= | | 9x-8x=-2 | | G=7/4(p-23) | | 3n^4+11n^2-20=0 | | 77=5w-8 | | 2x-7+8x=-5+18 | | 8y-9x=0 | | X/3=100 | | 19(6)+187= | | 16=k/111 | | 3n^4+11n-20=0 | | .9x-.6=-.6 | | -16x^2+50x=6 | | -3v-4v=-21 | | 4x^2-20x+100=100 | | (15a^4b^2c^3)/(5ac^5) | | f(2a)=3x^2+2x-5 | | 41=320-r | | 7/112=p-3/8 | | 7n^2(7n-4)= | | 8x-3+5x+4=79 | | 5b+7-3=26 | | 6x+48=9x-12 | | 30-8x-3=2 | | 5-c=-2 | | -3(h+4)=5(h-2) | | 4x^2-20x+0=0 |